224k views
3 votes
Please I need help with differential equation. Thank you

Solve: dt(y+y1/2)/(1-t)=dy(t+1)

1-Determine the interval of validity for the above solution.

2- Redo the above differential equation given that y(-1/2)=1

1 Answer

6 votes

1. I suppose the ODE is supposed to be


\mathrm dt(y+y^(1/2))/(1-t)=\mathrm dy(t+1)

Solving for
(\mathrm dy)/(\mathrm dt) gives


(\mathrm dy)/(\mathrm dt)=(y+y^(1/2))/(1-t^2)

which is undefined when
t=\pm1. The interval of validity depends on what your initial value is. In this case, it's
t=-\frac12, so the largest interval on which a solution can exist is
-1\le t\le1.

2. Separating the variables gives


(\mathrm dy)/(y+y^(1/2))=(\mathrm dt)/(1-t^2)

Integrate both sides. On the left, we have


\displaystyle\int(\mathrm dy)/(y^(1/2)(y^(1/2)+1))=2\int(\mathrm dz)/(z+1)

where we substituted
z=y^(1/2) - or
z^2=y - and
2z\,\mathrm dz=\mathrm dy - or
\mathrm dz=(\mathrm dy)/(2y^(1/2)).


\displaystyle\int(\mathrm dy)/(y^(1/2)(y^(1/2)+1))=2\ln|z+1|=2\ln(y^(1/2)+1)

On the right, we have


\frac1{1-t^2}=\frac12\left(\frac1{1-t}+\frac1{1+t}\right)


\displaystyle\int(\mathrm dt)/(1-t^2)=\frac12(\ln|1-t|+\ln|1+t|)+C=\ln(1-t^2)^(1/2)+C

So


2\ln(y^(1/2)+1)=\ln(1-t^2)^(1/2)+C


\ln(y^(1/2)+1)=\frac12\ln(1-t^2)^(1/2)+C


y^(1/2)+1=e^{\ln(1-t^2)^(1/4)+C}


y^(1/2)=C(1-t^2)^(1/4)-1

I'll leave the solution in this form for now to make solving for
C easier. Given that
y\left(-\frac12\right)=1, we get


1^(1/2)=C\left(1-\left(-\frac12\right)^2\right))^(1/4)-1


2=C\left(\frac54\right)^(1/4)


C=2\left(\frac45\right)^(1/4)

and so our solution is


\boxed{y(t)=\left(2\left(\frac45-\frac45t^2\right)^(1/4)-1\right)^2}

User Jwpol
by
5.4k points